Analysis of the Implementation of Law Number 11 of 2020 Concerning Job Creation on Labor Protection in the Garment Convection Industry - Pratika Gunareksa; Sulismadi Sulismadi (International Journal Labs, 2026)
This study aims to analyze the implementation of recruitment systems, employment contracts, labor protection, and social security in a local garment enterprise, assessing their conformity with Law Number 11 of 2020 concerning Job Creation. This study contributes novelty by examining the practical implementation gaps between labor regulations and actual practices in the small-scale garment industry, an area that remains underexplored in Indonesian labor law scholarship. This research adopts a qualitative descriptive approach using in-depth interviews with the garment company’s management. The collected data are analyzed based on key labor indicators, including recruitment and employment contracts (PKWT/PKWTT), wage protection, occupational health and safety (K3), and workers’ rights such as leave, overtime, and participation in social security programs (BPJS). Findings indicate that the recruitment and contractual systems generally follow company standard operating procedures, though implementation remains limited due to fluctuating sales performance. The study concludes that labor protection in the garment sector is relatively well-managed through regulated working hours, wage compliance, and inclusion in BPJS programs. The enforcement of Law Number 11 of 2020 on Job Creation has had a positive impact on the harmonization of workers’ rights, benefits, and wage systems. Nevertheless, unstable market conditions continue to hinder full policy implementation. Strengthening government support and local product competitiveness is essential to ensure the sustainability of Indonesia’s garment industry.